DESIGN AND CHARACTERIZATION OF LOW-POWER LOW-NOISE ALLDIGITAL SERIAL LINK FOR POINT-TO-POINT COMMUNICATION IN SOC - ALSER, MOHAMMED H K (2013)
The fully-digital implementation of serial links has recently emerged as a viable alternative to their classical analogue counterpart. Indeed, reducing the analogue content in favour of expanding the digital content becomes more attractive due to the ability to achieve less power consumption, less sensitivity to the noise and better scalability across multiple technologies and platforms with inconsiderable modifications. In addition, describing the circuit in hardware description languages gives it a high flexibility to program all design parameters in a very short time compared with the analogue designs which need to be re-designed at transistor level for any parameter change. This can radically reduce cost and time-to-market by saving a significant amount of development time. However, beside these considerable advantages, the fully-digital architecture poses several design challenges.